The Impact of Price Discounts and Viral Marketing on Purchase Intentions in TikTok E-commerce - Hamonangan, Yohanes; Bambang Sutejo (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2023)
In the current digital era, the role of social media, especially TikTok, has rapidly evolved and become an integral part of the daily lives of the global community. TikTok, a social network initially focused on short music videos, has transformed into an e-commerce platform that is changing the way we shop. With features like the “yellow cart”, TikTok enables content creators to market products and earn money from their sales. This research aims to determine the influence of viral marketing and discount promotions on purchase intention using a quantitative research method by utilizing a questionnaire in the form of a Google form, which will be distributed to the public by the researcher. This type of research is quantitative with an unspecified or unknown number of respondents. Using the Hair formula, the maximum sample size is 70 respondents for 7 indicators. In this study, the sample size is 70 respondents. The data analysis technique used in this research is multiple linear regression analysis using SPSS version 23 as the data processing tool. The results of this study indicate 37.2% of the variation in Price Discount can be explained by the variables Viral Marketing and Price Discount. the effect of Viral Marketing and Price Discount have a significant influence on Purchase Intention.